Complexity in high-temperature superconductors: General Aspects - Alvarez, G.; Moreo, A.; Dagotto, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
A spin-fermion and Landau–Ginzburg model for high-temperature superconductors are formulated and analyzed with unbiased numerical techniques. The study of the competition betweend-wave superconductivity and antiferromagnetism in the clean limit suggests that the phase diagramis not universal. When chemical disorder is considered, a «clustered state» with short range order but without long range order appears leading to the possibility of a giant proximity effect. The influence of disorder on the spectral function is also addressed and results are compared to available angle resolved photoemission data for cuprates.